Exploring the Determinants of Digital Payment Adoption for Philanthropic Activities in Mosques: Evidence from Banjarbaru, Indonesia - Mairijani Mairijani; Anna Salsabela; Andriani; Rizky Fadhillah; Muhammad Buya Al-Madany Abror; Nurhidayati (International Journal of Islamic Business and Economics (IJIBEC), 2026)
This study aims to examine the influence of perceived ease of use, security, and compliance with Sharia principles on mosque congregants’ intention to use QRIS (Quick Response Code Indonesian Standard) as a digital payment instrument for infaq and sadaqah in Banjarbaru City, Indonesia. Employing a quantitative survey approach, data were collected through an online questionnaire distributed via Google Forms to congregants from five mosques that have implemented QRIS payment services, namely the Al-Munawwarah Grand Mosque, Hidayatullah Muhajirin Jami Mosque, Kanzul Khairat Mosque, Baburrayyan Mosque, and Miftahul Khairat Mosque. Prior to completing the questionnaire, respondents were screened based on their experience in using QRIS for charitable transactions. A total of 154 respondents participated in the study, predominantly female students and university students aged 12–25 years. The collected data were analyzed using multiple linear regression with IBM SPSS Statistics version 21. The findings reveal that perceived ease of use, security, and Sharia compliance simultaneously exert a positive and significant influence on the intention to use QRIS for mosque-based Islamic philanthropy. Among these variables, Sharia compliance emerges as the most influential factor in encouraging QRIS adoption. These findings imply that the successful implementation of digital Islamic philanthropy platforms depends not only on technological convenience and transaction security but also on the integration of Islamic values and Sharia legitimacy. Consequently, mosque administrators, Islamic financial institutions, and policymakers should strengthen Sharia-oriented digital payment governance, enhance public trust in fintech systems, and promote digital literacy to accelerate the adoption of QRIS in mosque-based charitable activities.